Module to scaffold the process of filling grant documents in English - Cofiya Swartz; Elvira E. Valeeva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In order for students and professors to advance their educational and professional careers as well as become competitive specialists in the modern world of science and technology, it is essential for them to apply for international grant programs that allow them to take part in internships abroad. Currently, there are several foreign programs offered in Russia that provide financial support for students to participate in internships abroad. Unfortunately, studentsstudying in Russia often do not possess the skills necessary to complete foreign language documents correctly. This barrier reduces their chance to successfully pass through several stages of the selection process to secure full financial support while competing amongst a large number of applicants. As a solution to this issue, the authors offer for a module to be introduced into existing curricula, which will teach students how to complete grant documents in English. This module can be introduced in foreign language courses at any level, that are aimed at preparing students to receive a higher education. The content of the module was developed based on the analysis of foreign practices of studying an academic letter, which includes in itself, the preparation of the necessary documentation for grant programs. The module consists of an overview lecture that outlines different grant programs and their English language websites, where a full list of the necessary documentation needed to apply to the respective program is included. In order to submit a strong application for an international internship opportunity, a student should comprehend the rules of writing a statement of purpose as well as recommendation letters. Applicants should also be prepared to answer questions presented to them during an interview with representatives of the program for which they have applied. The main goal of the proposed module is to teach students how to effectively communicate per the requirements and objectives set forth by these grant programs. This module will allow for the development of critical thinking skills necessary to present application materials in a logical and structured manner, in both Russian and English.